Nutrient use and dynamics under different fertigation scheduling for banana (Musa paradisiaca) cultivation in vertisol - D, PAWAR D; D, KALE K; S K, DINGRE (The Indian Journal of Agricultural Sciences, 2014)
Field experiment was conducted at Mahatma Phule Krishi Vidyapeeth, Rahuri (Maharashtra) for three consecutive years (2008-2011) to study the nutrient availability, uptake and movement in vertisol under drip fertigation for banana (Musa paradisiaca L.) cv Grand naine. The drip fertigation @ 100, 80 and 60 per cent of recommended dose through water soluble fertilizers (WSF) applied in two schedules and results were compared with three control treatments. The drip fertigation @ 100 per cent recommended dose scheduled as per crop growth stages showed 46.22 per cent increase in yield (82.94 tonnes/ha). However, it was on par with 80% fertigation treatment (79 tonnes/ha) whereas, 60 per cent fertigation (Schedule as per crop growth stages) resulted into 40 per cent fertilizer saving and 24.5 per cent increase in yield over surface irrigation (57.40 tonnes/ha). The drip fertigation relatively improved the nutrients availability and uptake as compared to band placement of dry fertilizers. The study indicated that application of water soluble fertilizers through drip as per the growth stages proved superior as compared to uniform splits for periodical availability of nutrients, uptake and nutrient movement in soil than conventional fertilizers. The maximum movements of nutrients in vertisol were recorded for 100 and 80% fertigation using water soluble fertilizers. The N was moved up to 45 cm laterally and 60 cm vertically. P was moved up to 30 cm laterally and 40 cm vertically and K movement was up to 45 cm laterally and 60 cm vertically during the crop growth. The 100% fertigation, also registered higher economical parameters, however the difference with 80% fertigation was non significant.